1974
DOI: 10.1172/jci107551
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Immune Lysis of the Red Cells in Hereditary Erythroblastic Multinuclearity with a Positive Acidified Serum Test and Paroxysmal Nocturnal Hemoglobinuria

Abstract: A B S T R A C T The red cells of patients with hereditary erythroblastic multinuclearity with a positive acidified serum test (HEMPAS), a form of congenital dyserythropoietic anemia, and the cells of patients with paroxysmal nocturnal hemoglobinuria (PNH) are lysed more readily than normal cells by certain antibodies, notably cold agglutinins (anti-I) and complement. With some but not other examples of anti-I, HEMPAS and PNH cells adsorbed more antibody than normal cells. Equal quantities of adsorbed antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

1976
1976
2010
2010

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 28 publications
3
30
0
1
Order By: Relevance
“…Complement-coated cells were assayed for total C3 using a method previously described (14). The assay measures inhibition of lysis of C3-coated, trypsinized sheep cells by anti-C3 in the presence of guinea pig serum in a manner analogous to the IgG assay.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Complement-coated cells were assayed for total C3 using a method previously described (14). The assay measures inhibition of lysis of C3-coated, trypsinized sheep cells by anti-C3 in the presence of guinea pig serum in a manner analogous to the IgG assay.…”
Section: Methodsmentioning
confidence: 99%
“…In sensitizing a series ofrabbits with C3 antigen by methods previously described (14), the antiserum from a single rabbit was found to detect antigens present on native C3, and on C3b-and C3d-coated red cells. The The time-course of lysis ofanti-D-coated, washed red cells was rapid, with 70-80% of total observed lysis completed within 3.5 h (see Fig.…”
Section: C3bmentioning
confidence: 99%
See 1 more Smart Citation
“…The first definitive evidence of the nature of the aberrant interactions of complement with PNH erythrocytes was provided by a series of elegant experiments reported by Rosse and colleagues (3,4). Those studies showed that when complement was activated by either the classical or alternative pathway, PNH erythrocytes bound much greater amounts of activated C3 than normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Both PNH II and PNH III cells fix more complement (C)3b when complement is activated by either the classical or the alternative pathway (3)(4)(5)(6). This greater binding of C3b is due to the enhanced functional activity of the C3 convertase when affixed to these abnormal cells.…”
Section: Introductionmentioning
confidence: 99%